2017
DOI: 10.1111/jora.12303
|View full text |Cite
|
Sign up to set email alerts
|

Early Sexual Initiation and Mental Health: A Fleeting Association or Enduring Change?

Abstract: The present research examined how the within-person association between sexual initiation and internalizing symptoms decays over time, using data with annual measurement occasions across adolescence (N = 1,789) and statistical models of within-person change. Sexual initiation was associated with increased levels of internalizing symptoms for early-initiating girls (9th grade, approximately age 15), but not for on-time-initiating girls or for boys. The association between girls’ early sexual initiation and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Those without a history of the early sexual debut were more likely about 7% to be satisfied with life as compared to those with early sexual debut history. Negative emotional responses to first sexual encounters may also be influenced by psychological factors such as regret or a lack of readiness, which are more common in people who initiate sexual activity early than their on-time initiating peers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those without a history of the early sexual debut were more likely about 7% to be satisfied with life as compared to those with early sexual debut history. Negative emotional responses to first sexual encounters may also be influenced by psychological factors such as regret or a lack of readiness, which are more common in people who initiate sexual activity early than their on-time initiating peers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that emotional health outcomes of sexual behavior differ by age (Vasilenko et al, 2016;Meier, 2007;Wesche, Kreager et al, 2017), the association of CSREs with emotional outcomes may also differ by age. Mendle et al (2013) found that associations between CSREs and emotional health were stronger for younger adolescents; however, Manning et al (2005) found that associations between CSREs and emotional health did not differ by age.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Early sexual behaviour may have different health and behavioural outcomes for males and females. Research has associated early sexual initiation among girls with increased levels of internalising symptoms, although this effect may decline over time affecting adult women less [ 11 , 18 ]. Early initiating girls are less likely to use condoms and other contraceptives at first sex, increasing their risk of pregnancy and Sexually Transmitted Infections (STIs), and are more likely to engage in subsequent sexual risk taking behaviour in adolescence and later in life [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%